Spółka celowa (SPV) jako instrument realizacji przedsięwzięć w formule partnerstwa publiczno-prywatnego z perspektywy podmiotu publicznego - Pocztowski, Bartłomiej (Kwartalnik Prawa Publicznego, 2015)
The realization of public tasks is the basic responsibility of the functioning of the public sector. However, it brings a lot of expenses which are difficult to cover. The Act on Public-Private Partnership which came into force on the 19th of December 2008 proposed the possibility to conclude an agreement and then to create a special purpose vehicle (SPV) by the public and private partners (the SPV may takes a form of i.e. joint stock company, a limited liability company). The choice of this mode of operation should be preceded by a detailed analysis that answers the question of whether it is possible to realize the task in the form of a special purpose vehicle. SPV is a tool that should be “tailor-made” and adapted to the to the specific character of a given project. In reference to the provisions of the Public-Private Partnership Act, it should be noted that the interest of the public partner shall be effectively protected.